Anxiety relief for teens : essential CBT skills and mindfulness practices to overcome anxiety and stress - Galanti, Regine (Zeitgeist, 2020)
With proven CBT-based skills and mindfulness techniques, this book can be your guide out of the spiraling stress of anxiety and get you back on track to living a happy and healthy life. Getting good grades, keeping up with social media, maintaining friendships... you have a lot on your plate and it's more difficult when you add anxiety to the mix. You may even be avoiding situations, events, or people that could trigger your anxiety. So, how do you stop yourself from missing out on life' With Anxiety Relief for Teens, Dr. Regine Galanti teaches you how CBT-based skills and mindfulness techniques can help you manage your anxiety and reverse negative patterns. Through simple and effective exercises that help you change your thoughts, behaviors, and physical reactions, this helpful guide gives you the tools you need to navigate all of life's challenges. Anxiety Relief for Teens features: Quizzes and self-assessments to better understand your anxiety and emotions and discover their respective triggers. 30+ CBT-based tools to manage your anxiety along with practical strategies for dealing with challenging emotions such as anger and sadness. 30+ mindfulness practices to cope with your anxiety in the present moment through visualizations, breathing, meditation, and other exercises.